2022
DOI: 10.3390/ma15093228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Tooling Techniques of Medical Titanium Implants on Bacterial Biofilm Formation In Vitro

Abstract: The aim of this study was to assess the biofilm formation of Streptococcus mutans, Staphylococcus aureus, Enterococcus faecalis, and Escherichia coli on titanium implants with CAD-CAM tooling techniques. Twenty specimens of titanium were studied: Titanium grade 2 tooled with a Planmeca CAD-CAM milling device (TiGrade 2), Ti6Al4V grade 5 as it comes from CAD-DMLS device (computer aided design-direct metal laser sintering device) (TiGrade 5), Ti6Al4V grade 23 as it comes from a CAD-CAM milling device (TiGrade 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This study finds that the biofilm formation of S. mutans favors PLA over titanium, whereas S. aureus binds more strongly to titanium. Another major result was that salivary coating increased biofilm formation on both implant materials tested by all four bacterial strains in a statistically significant manner, which is in accordance with our previous studies [15,16]. Another study has also reported high bacterial adherence to implant material with saliva contamination [17], which might be because the presence of salivary pellicles on the implant surface reduces the chemical charge and make it more hydrophilic to favor the attachment of bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…This study finds that the biofilm formation of S. mutans favors PLA over titanium, whereas S. aureus binds more strongly to titanium. Another major result was that salivary coating increased biofilm formation on both implant materials tested by all four bacterial strains in a statistically significant manner, which is in accordance with our previous studies [15,16]. Another study has also reported high bacterial adherence to implant material with saliva contamination [17], which might be because the presence of salivary pellicles on the implant surface reduces the chemical charge and make it more hydrophilic to favor the attachment of bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…All implants were manufactured as 20 mm discs, sterilized, and destained in a similar way as normally provided for the needs of the patients. The implant types studied were PEEK, titanium grade 2, and titanium grade 5 [14].…”
Section: Peek and Titanium Implant Preparationmentioning
confidence: 99%
“…Nevertheless, studies have shown that the surface structure of commonly used titanium implant materials is relatively rough, which promotes the formation of biofilm. 38–40 As a result, research has been conducted on modifying the properties of implant materials by optimizing wettability, topography, and pattern size to prevent biofilm formation. 41 Several studies have utilized nanoimprint lithography as a patterning technique to create hierarchically patterned samples.…”
Section: Discussionmentioning
confidence: 99%